THE EFFECTIVENESS OF A COGNITIVE PROGRAM DIRECTED AT CHILDREN WITH STUTTERING FROM 6 TO 12 YEARS OF AGE - Saifi Abderrahim,; Abla Mahrez, (International Journal of Innovative Technologies in Social Science, 2025)
In this study, we aim to analyze the effectiveness of cognitive programs targeting children who stutter between the ages of 6 and 12 years, from a psychological and social theoretical perspective. We explore the theoretical foundations of stuttering and its psychological and social impacts, focusing on the central role of cognitive factors in the continuation of this cycle. The study examines the essential components of cognitive programs, including cognitive restructuring, emotion management, and sociocognitive adaptation, and evaluates leading treatment models such as integrated programs and acceptance and commitment programs.The results reveal that cognitive programs significantly contribute to improving children's mental health and social integration by breaking the vicious cycle of negative thoughts and anxiety that fuel the disorder. The study also highlights the importance of family and school support as an important factor in enhancing the effectiveness of these programs. We conclude this study by emphasizing the importance of adopting an integrated and comprehensive approach to stuttering treatment, combining cognitive and behavioral interventions with environmental support.